Hopantomide in pediatric neurological practice: outlooks - O. A. Pylaeva (Русский журнал детской неврологии, 2021)
Hopantomide® is a drug containing calcium salt of hopantenic acid. The drug is registered and produced in Russia (Usolye-Siberian Chemical Pharmaceutical Factory) with the use of own raw materials and goes through a full production cycle, which guarantees quality control at every stage. Hopantomide belongs to nootropics and has neurometabolic, neuroprotective, and neurotrophic properties, as well as anticonvulsant action. According to the package insert and results of the studies evaluating the efficacy of hopantenic acid, Hopantomide has a number of positive therapeutic effects. It increases brain resistance to hypoxia and toxic substances, stimulates anabolic processes in neurons, improves mental and physical performance, combines moderate sedative action with mild stimulating effect, reduces motor excitability with simultaneous regulation of behavior, improves the metabolism of gamma-aminobutyric acid and normalizes its level in individuals with chronic alcohol intoxication and after alcohol withdrawal, has anxiolytic and thymoleptic properties, inhibits the abnormal bladder reflex and detrusor tone. This ensures high efficacy of Hopantomide in the treatment of various nervous diseases in different age groups. In our opinion, the combination of various positive effects of just one drug can significantly reduce the pharmacological burden. In this review, we discuss well-known and potential mechanisms of action, indications for its use with a focus on Hopantomide benefits in pediatric neurological practice, and studies evaluating the efficacy of hopantenic acid in clinical practice. Particular attention is paid to the possibilities of its use in children, including those with attention deficit hyperactivity disorder and developmental delay, as well as the part of combination therapy for epilepsy together with antiepileptic drugs.Drugs containing hopantenic acid are well tolerated by patients, including children who receive it for a long time.